URDU-SCIENTIFIC SERVICES OF MUSLIMS : AN ANALYTICAL STUDY OF ORIENTALIST ATTITUDES - Shagufta Naveed; Muhammad Irfan Ahmad (دی اسکالر)
The remarkable   Muslim role in promoting the universal human culture owes to their deep affiliation with knowledge, especially, the scientific one. They availed the old as well as the contemporary civilizations to seek knowledge of all kinds. Consequently, science, technology and the other advanced disciplines developed in the Muslim World. They rendered considerable services in developing the Greek scientific ideology and contributed a lot towards its development. The Muslims handed over these valuable disciplines to the other nations especially to Europe. The modern European civilization owes greatly to the Muslim World for its scientific and technological progress. Europe utilized these priceless disciplines and made a quick journey from the hell of ignorance towards the heaven of knowledge. A particular group of orientlists has been trying to deny the glorious scientific services of the Muslims. They propagate that the Muslims have not played any considerable role in this specific area of knowledge. It is the dire need of the hour to have a meaningful analysis of the philosophy and approach of the Orientalists. This, particular, article has been composed, especially, to fulfill the educational and analytical needs of the present world.